A Web-Based Tourism Recommendation System for Boyolali Using Content-Based Filtering and Cosine Similarity - Muhammad Naufal Arkan; Aris Puji Widodo; Guruh Aryotejo (Department of Informatics, Universitas Diponegoro, 2026)
Tourism is a primary economic driver for Boyolali Regency. However, destination information remains fragmented, lacking a personalized approach to meet diverse visitor preferences. To address this issue, this study developed